Transmission of prions within the gut and toward the central nervous system - Natale, Gianfranco (Landes Bioscience, 2011)
The prion protein is a glycoprotein characterized by a folded α-helical structure that, under pathological conditions, misfolds and aggregates into its infectious isoform as β-sheet rich amyloidic deposits. The accumulation of the abnormal protein is responsible for a group of progressive and fatal disorders characterized by vacuolation, gliosis and spongiform degeneration. Prion disorders are characterized by a triple aetiology: familial, sporadic or acquired, although most cases are sporadic. The mechanisms underlying prion neurotoxicity remain controversial, while novel findings lead to hypothesize intriguing pathways responsible for prion spreading. The present review aims to examine the involvement of the gastrointestinal tract and hypothesizes the potential mechanisms underlying cell-to-cell transmission of the prion protein. In particular, a special emphasis is posed on the mechanisms of prion transmission within the gut and towards the central nervous system. The glycation of prion protein to form advanced glycation end-products (AGE) interacting with specific receptors placed on neighboring cells (RAGE) represents the key hypothesis to be discussed.